Polemical and exegetical polarities in medieval Jewish cultures: Studies in Honour of Daniel J. Lasker - Krinis, Ehud; Bashir, Nabih; Ofenberg, Śarah; Tsadiḳ, Shalom; Lasḳer, Daniʾel (Studia Judaica, 2021)
Frontmatter -- Acknowledgement -- Contents -- I On Daniel J. Lasker and his Scholarship -- Prof. Daniel J. Lasker – Scholar, Teacher, and Friend -- Daniel J. Lasker and His Treatment of Jewish Polemics -- List of Publications -- II Jewish Polemics and Exegesis in the Islamicate World -- Polemical Logic: Al-Muqammaṣ’s Refutation of Christianity -- The Role of Gog in Daniel al-Qūmisī’s Eschatology -- Theological Consideration of the Gift of the Land and the Radical Treatment of the “Seven Nations” in Medieval Judeo-Arabic Exegesis -- Epistemology in the Service of Polemic: Yūsuf al-Baṣīr’s Kitāb al-Istiʿānah: Text and Translation -- Maimonides on the Status of Judaism -- Abraham Maimonides on Reclaiming Judaism’s Lost “Perfection” from the “Imperfection” of Islam -- III Jewish and Anti-Jewish Polemic and Exegesis in the Christian World -- Abraham bar Ḥiyya (d. ca. 1136) on “The Pure Soul” -- Asmakhtaʾ and Abraham ibn Ezra’s Exegesis -- The Finding of the “True Cross” in Judah Hadassi’s Eškol ha-Kofer and the Polemical Parody Toledot Yešu -- The Book of Nestor the Priest and the Toledot Yešu in the Polemics of Abner of Burgos/Alfonso of Valladolid -- Rashi on Isaiah 53: Exegetical Judgment or Response to the Crusade? -- “The Best of Snakes. . .”: A Polemical Midrash in the Rashi Supercommentary Tradition -- The Discussion of the Messiah in Crescas’s Refutation -- Joshua Ha-Lorki on the Meaning of Emunah: Between Religion and Faith -- Jewish Anti-Semites: The Case of Medieval Apostates -- Daniel in the Lions’ Den: Jewish-Christian Polemics in Medieval Text and Image -- IV Jewish-Jewish and Jewish-Christian Relations -- Understanding the Uneven Reception of Rabbenu Tam’s Taqqanot -- Ritual Imagery Gone Wrong: A Fifteenth-Century Siddur in a Christian Workshop -- Transliteration Charts -- Index of Names